The Current Status, Hot Topics And Trends Of Environmental, Social And Governance (ESG) Research In East Asian Countries: A Bibliometric Analysis - Qiaoyang, Zheng; Talib , Zunirah Mohd; Qiaoyang, Zheng (Journal of Ecohumanism, 2024)
East Asian countries are experiencing rapid development in environmental, social, and governance (ESG) practices. As an effective measure for green and sustainable development, ESG is widely implemented within enterprises and has a profound impact on socio-economic development. This article employs CiteSpace visualisation software to analyse 3,279 documents related to ESG published from 2004 to 2024, as indexed in the Web of Science (WOS) database. The analysis focuses on publication timelines, countries, authors, highly cited literature, and keyword clustering to explore the hotspots and trends in ESG research among East Asian countries. The findings indicate a significant increase in ESG publications in recent years, with research hotspots and trends primarily centred around sustainable development, corporate social responsibility, sustainability reporting, environmental regulation, and ESG performance. Although there is considerable collaboration among countries, the overall research remains in its early stages, with few high-output and high-impact authors, resulting in a dispersed research effort. This article serves as a reference for researchers to quickly grasp the current state of ESG development in East Asian countries and to identify research hotspots and trends.